Cheetah interspecific SCNT followed by embryo aggregation improves in vitro development but not pluripotent gene expression - Moro, Lucía Natalia (2015)
The aim of this study was to evaluate the capacity of domestic cat (Dc, Felis silvestris) oocytes to reprogram the nucleus of cheetah (Ch, Acinonyx jubatus) cells by interspecies SCNT (iSCNT), by using embryo aggregation. Dc oocytes were in vitro matured and subjected to zona pellucida free (ZP-free) SCNT or iSCNT, depending on whether the nucleus donor cell was of Dc or Ch respectively. ZP-free reconstructed embryos were then cultured in microwells individually (Dc1X and Ch1X groups) or in couples (Dc2X and Ch2X groups). Embryo aggregation improved in vitro development obtaining 27.4, 47.7, 16.7 and 28.3% of blastocyst rates in the Dc1X, Dc2X, Ch1X and Ch2X groups, respectively (P<0.05). Moreover, aggregation improved the morphological quality of blastocysts from the Dc2X over the Dc1X group. Gene expression analysis revealed that Ch1X and Ch2X blastocysts had significantly lower relative expression of OCT4, CDX2 and NANOG than the Dc1X, Dc2X and IVF control groups. The OCT4, NANOG, SOX2 and CDX2 genes were overexpressed in Dc1X blastocysts, but the relative expression of these four genes decreased in the Dc2X, reaching similar relative levels to those of Dc IVF blastocysts. In conclusion, Ch blastocysts were produced using Dc oocytes, but with lower relative expression of pluripotent and trophoblastic genes, indicating that nuclear reprogramming could be still incomplete. Despite this, embryo aggregation improved the development of Ch and Dc embryos, and normalized Dc gene expression, which suggests that this strategy could improve full-term developmental efficiency of cat and feline iSCNT embryos.